A thin film sensor for enhancing ultrasonic reflection echo and its application

By optimizing the structure in the piezoelectric thin film sensor, increasing the electrode layer thickness and forming a mixing area between the pre-plating coating and the electrode coating, the problem of poor ultrasonic stress detection effect on high-temperature alloy bolts is solved, and the acquisition of strong ultrasonic signals is achieved and the success of stress detection.

CN116989829BActive Publication Date: 2025-02-14WUHAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310837102.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-02-14
Estimated Expiration
2043-07-07

AI Technical Summary

Technical Problem

The prior art is difficult to achieve effective ultrasonic stress detection on high-temperature alloy bolts with severe wave absorption. It is mainly because ultrasonic waves are scattered when propagating inside the bolt, and the sound wave energy is absorbed by the material, resulting in a low signal-to-noise ratio and it is difficult to obtain higher reflection back. Wave.

Method used

By optimizing the sensor structure, increasing the thickness of the electrode layer, and forming a mixing area of ​​pre-plating coating and electrode coating on the piezoelectric coating surface, the deposition parameters of the electrode coating are regulated to improve coating quality and reduce the acoustic frequency, thereby enhancing ultrasound Reflection echo.

Benefits of technology

It realizes the acquisition of strong ultrasonic signals on high-temperature alloy bolts, reduces the material's absorption of sound wave energy, improves the reflected ultrasonic amplitude and signal-to-noise ratio, and successfully realizes stress detection on high-temperature alloy bolts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116989829B_ABST
    Figure CN116989829B_ABST
Patent Text Reader

Abstract

The present invention discloses a thin film sensor for enhancing ultrasonic reflection echo and its application. The sensor includes, from bottom to top, a substrate, a piezoelectric coating and an electrode coating; the thickness of the electrode coating is 5 to 100 μm and is prepared by magnetron sputtering; the composition of the electrode coating includes at least one of Ag, Cu, Cr, Ti or Al. The present invention does not need to change the material and structure of the piezoelectric coating, forms a pre-plating coating and an electrode coating on the surface of the piezoelectric coating, and applies a bias voltage during the preparation of the electrode coating to form a mixed zone of the pre-plating coating and the electrode coating to enhance the bonding force between the electrode coating and the pre-plating coating. The obtained sensor for enhancing ultrasonic reflection echo reduces the absorption of acoustic wave energy by the substrate, improves the amplitude and signal-to-noise ratio of the reflected ultrasonic wave, and realizes efficient stress detection of the substrate. The sensor of the present invention also obtains a strong ultrasonic signal on a high-temperature alloy bolt with severe wave absorption, broadening the application of ultrasonic stress detection in high-temperature alloy bolts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of piezoelectric sensors, and in particular to a thin film sensor for enhancing ultrasonic reflection echoes and applications thereof. Background Art

[0002] Bolts and other fasteners are the core components of large-scale equipment such as aerospace and energy. Bolt preload is a necessary condition to ensure its safe and reliable operation. Existing technologies such as torque method, color method, laser grating method, etc. have serious deficiencies in the measurement of preload, large errors, and affect the strength of bolts. New preload measurement technologies are urgently needed. Piezoelectric film sensors and detection technology, based on the acoustic elastic effect, can achieve accurate measurement of preload and have broad market application prospects.

[0003] The most critical part of the preload monitoring technology of piezoelectric film sensors is the piezoelectric coating. That is, when the object to be measured is under stress, the speed of the ultrasonic wave excited by the piezoelectric coating will change with the stress value. By calibrating the relationship curve between the ultrasonic sound time or flight time and the preload force, the stress can be measured through the ultrasonic flight time.

[0004] However, even the best piezoelectric materials cannot meet the stress detection requirements of all objects to be tested. For materials with severe wave absorption, such as high-temperature alloy bolts, the microstructure of high-temperature alloys is generally austenite, with relatively coarse and uneven grains. In addition, due to the existence of grain boundary strengthening and precipitation strengthening, the sound velocity has anisotropy and sound transmission characteristics, that is, during the propagation of ultrasonic waves inside the bolt, the scattering is enhanced, and the sound wave energy is easily absorbed by the bolt material, resulting in a grass-like echo, a very low signal-to-noise ratio, and it is difficult to obtain a high reflection echo, so stress detection cannot be achieved.

[0005] Therefore, it is necessary to improve the ultrasonic detection effect of high-temperature alloy bolts through structural improvement, material innovation and other technologies. Summary of the invention

[0006] In order to obtain ultrasonic signals and realize stress detection on high-temperature alloy bolts with severe wave absorption, the present invention optimizes the sensor structure design, appropriately increases the thickness of the electrode layer to obtain higher coating quality and reduces the sensor sound wave frequency, thereby achieving the effect of enhancing ultrasonic reflection echo and achieving strong ultrasonic signals on high-temperature alloy bolts.

[0007] In order to achieve the above object, the present invention provides a thin film sensor for enhancing ultrasonic reflection echo, which comprises, from bottom to top, a substrate, a piezoelectric coating and an electrode coating;

[0008] The electrode coating has a thickness of 5 to 100 μm and is prepared by magnetron sputtering; the composition of the electrode coating includes at least one of Ag, Cu, Cr, Ti or Al.

[0009] Further, the preparation of the electrode coating comprises,

[0010] The deposition time is 10 to 500 minutes at a RF power of 300 to 900 W, an Ar gas flow rate of 0.6 Pa to 2.0 Pa, a deposition temperature of 40 to 150 ° C, and a target-substrate distance of 40 mm to 90 mm. That is, the deposition rate (i.e., thickness) of the electrode coating can be controlled by adjusting these deposition parameters.

[0011] Furthermore, there is a 50-200 nm pre-plating coating between the piezoelectric coating and the electrode coating;

[0012] The method for preparing the pre-plating coating comprises:

[0013] The arc ion plating method is adopted, with the arc current of 80-120A, the Ar gas flow rate of 0.6-2.0Pa, the deposition temperature of 40-150°C, the target-substrate distance of 100-200mm, and the deposition time of 30s-2min.

[0014] Furthermore, the pre-plating coating comprises at least one of Cr, Ti or Al.

[0015] Furthermore, there is a mixed zone of the pre-plating coating and the electrode coating between the pre-plating coating and the electrode coating;

[0016] The mixed zone of the pre-plating coating and the electrode coating is formed by adjusting the duty cycle to 20% to 50%, the current to 0.2A to 0.8A, and applying a bias voltage of 100 to 300V during the initial 30s to 2min of preparing the electrode coating by magnetron sputtering.

[0017] Furthermore, the thickness of the mixed zone of the pre-plating coating and the electrode coating is 10 to 30 nm.

[0018] Further, the composition of the piezoelectric coating includes one of ZnO, AlN, AlScN, and LiNbO3;

[0019] The method for preparing the piezoelectric coating comprises:

[0020] The RF power is 500-900W, the deposition gas pressure is 0.6Pa-2.0Pa, the flow ratio of Ar gas to functional gas is 3 / 1-1 / 3, the deposition temperature is 40-250°C, the target-substrate distance is 30mm-90mm, and the deposition time is 10-500min.

[0021] Furthermore, the substrate includes a stainless steel plate and high-temperature alloy bolts.

[0022] The present invention also provides the application of the above-mentioned thin film sensor for enhancing ultrasonic reflection echo in stress detection.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention forms a pre-plating coating and an electrode coating on the surface of the piezoelectric coating without changing the material and structure of the piezoelectric coating. A bias voltage is applied during the preparation of the electrode coating to form a mixed zone between the pre-plating coating and the electrode coating, thereby enhancing the bonding force between the electrode coating and the pre-plating coating, thereby optimizing the sensor structure, and further appropriately increasing the thickness of the electrode layer to obtain a higher coating quality and reduce the acoustic wave frequency of the sensor. The obtained thin film sensor with enhanced ultrasonic reflection echo reduces the substrate's absorption of acoustic wave energy, increases the reflected ultrasonic amplitude and signal-to-noise ratio, and realizes efficient stress detection of the substrate.

[0025] (2) Previous studies have shown that when ultrasonic waves propagate inside high-temperature alloy bolts, the scattering is very strong and the sound wave energy is easily absorbed by the bolt material, resulting in a grass-like echo with a very low signal-to-noise ratio, making it difficult to obtain a good reflected echo. The thin film sensor for enhancing ultrasonic reflected echo of the present invention can also obtain a strong ultrasonic signal on high-temperature alloy bolts with severe wave absorption, thus broadening the application of ultrasonic stress detection in high-temperature alloy bolts. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 The schematic diagram of the structure of the thin film sensor for enhancing ultrasonic reflection echo prepared in the most preferred embodiment of the present invention is shown;

[0028] Figure 2 The ultrasonic signals and ultrasonic frequencies of the thin film sensors for enhancing ultrasonic reflection echo prepared in Examples 1 to 4 of the present invention are shown, wherein: Figure 2 (a) and Figure 2 (c) is the ultrasonic echo frequency; Figure 2 (b) and Figure 2 (d) is the ultrasonic signal;

[0029] Figure 3 The ultrasonic signals and ultrasonic frequencies of the thin film sensors for enhancing ultrasonic reflection echo prepared in Examples 5 to 10 of the present invention are shown, wherein: Figure 3 (a) is the ultrasonic signal diagram, Figure 3 (b) Ultrasonic echo frequency, Figure 3 (c) Ultrasonic signal amplitude and frequency numerical line graph, Figure 3(d) is the corresponding time-of-flight (TOF) data;

[0030] Figure 4 The ultrasonic signals and ultrasonic frequencies of the thin film sensors for enhancing ultrasonic reflection echo prepared in Examples 11 to 14 of the present invention are shown, wherein: Figure 4 (a) is the ultrasonic signal diagram, Figure 4 (b) Ultrasonic echo frequency, Figure 4 (c) Ultrasonic signal amplitude and frequency numerical line graph, Figure 4 (d) is the corresponding TOF data;

[0031] Figure 5 The ultrasonic signals and ultrasonic frequencies of the thin film sensors for enhancing ultrasonic reflection echo prepared in Examples 15 to 18 of the present invention are shown, wherein: Figure 5 (a) is the ultrasonic signal diagram, Figure 5 (b) Ultrasonic echo frequency, Figure 5 (c) Ultrasonic signal amplitude and frequency numerical line graph, Figure 5 (d) is the corresponding TOF data;

[0032] Figure 6 The ultrasonic signals and ultrasonic frequencies of the thin film sensors for enhancing ultrasonic reflection echo prepared in Examples 19 to 24 of the present invention are shown. Figure 6 (a) is the ultrasonic signal diagram, Figure 6 (b) Ultrasonic echo frequency, Figure 6 (c) Ultrasonic signal amplitude and frequency numerical line graph, Figure 6 (d) is the corresponding TOF data.

[0033] Figure 7 The relationship between the deposition rate of Ag, Cu, Cr, Ti, Al, and AgCr electrode coatings and the target-substrate distance obtained in Example 25 of the present invention is shown.

[0034] Figure 8 The relationship between the deposition rate of Ag and Cr electrode coatings and the radio frequency power obtained in Example 26 of the present invention is shown;

[0035] Description of reference numerals:

[0036] 1-substrate, 2-piezoelectric coating, 3-pre-plating coating, 4-mixed area of ​​pre-plating coating and electrode coating, 5-electrode coating. DETAILED DESCRIPTION

[0037] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention. The raw materials used in the present invention, unless otherwise specified, are conventional commercial products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.

[0038] The principle of enhancing ultrasonic reflection echo of the present invention is as follows:

[0039] ①The amplitude of the reflected echo is proportional to the excitation voltage and (k-mf 2 ), where m is the mass of the coating, f is the frequency of the sound wave, and k is the elastic coefficient of the piezoelectric layer (constant value). Therefore, only a constant excitation voltage is needed (i.e., the voltage applied when measuring ultrasonic signals. The excitation voltage will cause the particles inside the material to displace. If a high-frequency electric field is applied, the particles will vibrate at high frequencies, thereby generating ultrasonic waves). By adjusting the mass of the coating and the frequency of the sound wave, mf 2 The overall value increases, which can enhance the amplitude of the ultrasonic reflection echo.

[0040] ② Ultrasonic energy is affected by the transmission distance and its own frequency during transmission. If the frequency of the sound wave is too high, scattering and diffraction will occur, and it will be absorbed by the matrix and other materials, which will increase the loss of sound wave energy and shorten the transmission distance, which is not conducive to the measurement of ultrasonic signals with longer bolts as the base material. Therefore, the frequency of the ultrasonic wave can be reduced as much as possible to make it easier to transmit and enhance the penetration depth, which can enhance the amplitude of the ultrasonic reflection echo.

[0041] For the above two points, it can be seen that the second point requires reducing the frequency, and the first point requires increasing mf 2 value, so it should be controlled by design to obtain a lower frequency on the one hand and a larger mass on the other hand, and the increase in mass is higher than f 2 The value is reduced by a multiple, so that the above two principles of enhancing the amplitude of ultrasonic reflection echo can be met at the same time.

[0042] Based on this, in some embodiments of the present invention, high-quality Ag, Cu, Cr, Ti, Al, AgCr and other coatings are preferentially selected as electrode coatings, and the thickness of the electrode layer is appropriately increased to obtain higher coating quality and reduce the sensor sound wave frequency, so as to achieve the effect of enhancing the ultrasonic reflection echo.

[0043] Although a higher coating quality and a lower sensor frequency can be obtained by appropriately increasing the thickness of the electrode layer, the electrode layer and the piezoelectric coating are not sufficiently bonded, which will cause the deposited electrode layer to detach prematurely, affecting the performance of the sensor. Therefore, in some preferred embodiments of the present invention, in order to improve the bonding performance between the electrode coating and the piezoelectric coating, before depositing the electrode layer, a metal is pre-plated on the surface of the piezoelectric coating to form a pre-plated coating, and then the electrode coating is deposited on the pre-plated coating. The presence of the pre-plated coating also acts as a barrier layer to prevent the electrode coating from diffusing into the piezoelectric coating in a high temperature environment, thereby reducing the high temperature stability performance.

[0044] In the most preferred embodiment of the present invention, when depositing the electrode coating on the surface of the pre-plated coating, a bias voltage is applied in the initial short time. The bias voltage will enhance the kinetic energy of the raw material particles of the electrode coating, so that part of the electrode material particles are injected into the pre-plated coating, and a mixed zone of the pre-plated coating and the electrode coating is formed at the upper end of the pre-plated coating, which can further enhance the bonding force between the electrode coating and the pre-plated coating. The structure diagram of the thin film sensor for enhancing ultrasonic reflection echo in these most preferred embodiments is shown in FIG. Figure 1 , including a substrate 1, a piezoelectric coating 2, a pre-plating coating 3, a mixed area 4 of the pre-plating coating and the electrode coating, and an electrode coating 5, and the preparation steps are as follows:

[0045] Step 1: Prepare the magnetron sputtering equipment: place the piezoelectric target and substrate 1.

[0046] Step 2, depositing piezoelectric coating 2: adjust the RF power to 500-900W, the deposition pressure to 0.6Pa-2.0Pa, the flow ratio of Ar gas to functional gas to 3 / 1-1 / 3, the deposition temperature to 40-250°C, the target-substrate distance to 30mm-90mm, and the deposition time to 10-500min. The functional gas is selected according to the piezoelectric material to be deposited, for example, N2 when depositing AlN and O2 when depositing lithium niobate, and the piezoelectric coating 2 is deposited on the surface of the substrate 1;

[0047] Step 3, depositing the pre-plating coating 3: using arc ion plating to deposit the pre-plating coating 3 on the surface of the piezoelectric coating 2, the parameters are: arc current of 80-120A, Ar gas flow of 0.6-2.0Pa, deposition temperature of 40-150°C, target-base distance of 100-200mm, deposition time of 30s-2min;

[0048] Step 4, deposition of electrode coating 5: RF power is 300-900W, Ar gas flow is 0.6Pa-2.0Pa, deposition temperature is 40-150℃, target-substrate distance is 40mm-90mm, and deposition time is 10-500min. When depositing the electrode coating, a bias voltage of 100-300V is applied during the initial 30s-2min, and then the bias voltage is removed until the deposition is completed. The specific parameters of the bias voltage are: the substrate potential is lower than the target material, the voltage is between 100V and 300V, the duty cycle is between 20% and 50%, and the current is between 0.2A and 0.8A. The bias voltage will enhance the kinetic energy of the raw material particles of the electrode coating, so that part of the electrode material particles are injected into the pre-plating coating, forming a mixed zone 4 (about 10-30nm thick) of the pre-plating coating and the electrode coating, and increasing the bonding force between the electrode coating and the pre-plating coating.

[0049] In addition, in some embodiments of the present invention, the deposition rate and thickness of each electrode coating can be controlled by adjusting the RF power, Ar gas flow, deposition temperature, target-substrate distance, deposition time, etc.

[0050] The following will be combined with the specific embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] Example 1

[0052] A method for preparing a thin film sensor for enhancing ultrasonic reflection echo, the steps are as follows:

[0053] Step 1: Prepare the magnetron sputtering equipment: place the Al target and M8 high-temperature alloy bolts;

[0054] Step 2, depositing an AlN piezoelectric coating; depositing for 480 min at a radio frequency power of 900 W, a deposition pressure of 2.0 Pa, an Ar / N2 flow ratio of 1 / 1, a deposition temperature of 150° C., and a target-base distance of 5 cm, to deposit a 12 μm AlN piezoelectric coating on the surface of the high-temperature alloy bolt;

[0055] Step 3, depositing a pre-plated coating: using a high-purity Cr target, depositing for 1 min at an arc current of 90 A, an Ar gas flow rate of 1.0 Pa, a deposition temperature of 45° C., and a target-base distance of 120 mm, a 100 nm pre-plated Cr coating is deposited on the surface of the AlN piezoelectric coating;

[0056] Step 4, depositing electrode coating: using high-purity Ag target, depositing for 20 min at a RF power of 700 W, an Ar gas flow rate of 1.0 Pa, a deposition temperature of 45 ° C, and a target-substrate distance of 55 mm, adding bias voltage at the beginning of deposition for 1 min (the substrate potential is lower than the target, the voltage is 200 V, the duty cycle is 30%, and the current is 0.4 A) to promote the energy-carrying Ag ions to enter the Cr coating, forming a mixed zone of the Cr coating and the Ag coating with a thickness of about 20 nm to increase the bonding; then remove the bias until the deposition is completed, and deposit a 20 μm Ag coating on the surface of the pre-plated Cr coating.

[0057] Embodiments 2 to 4

[0058] It is basically the same as Example 1, with the only difference being that the deposition time in step 4 is 40 min, 50 min and 60 min respectively, and the prepared Ag coating has an enhanced ultrasonic reflection echo sensor with a thickness of 40 μm, 50 μm and 60 μm respectively.

[0059] The ultrasonic signals and ultrasonic frequencies (excitation voltage is 200V) of the sensors for enhancing ultrasonic reflection echo prepared in Examples 1 to 4 were tested. Figure 2 shown. Figure 2 (a) and Figure 2 (c) is the ultrasonic echo frequency; Figure 2 (b) and Figure 2 (d) is the ultrasonic signal. It can be seen that as the thickness of the Ag coating gradually increases, the coating mass increases, and the ultrasonic echo frequency gradually decreases, causing the reflected ultrasonic amplitude to gradually increase. When the Ag coating thickness is less than 20μm, the reflected ultrasonic wave cannot be measured. These results show that by adjusting the thickness of the Ag coating, not only a coating with a larger mass is obtained, but also the ultrasonic frequency is reduced to reduce the absorption of the sound wave energy by the high-temperature alloy material, thereby increasing the reflected ultrasonic amplitude and signal-to-noise ratio, and realizing stress detection of high-temperature alloy bolts.

[0060] Comparative Example 1

[0061] The process is basically the same as Example 1, with the only difference being that when depositing the Ag coating in step 4, no bias voltage is applied during the entire process.

[0062] The results show that the Ag coating prepared in Comparative Example 1 is directly separated from the surface of the Cr coating, no effective electrode structure is formed, and the ultrasonic signal drawn is 0. This proves that it is impossible to obtain an electrode coating with strong binding force without bias, which is not conducive to signal measurement.

[0063] Example 5

[0064] A method for preparing a thin film sensor for enhancing ultrasonic reflection echo, the steps are as follows:

[0065] Step 1: Prepare the magnetron sputtering equipment: place the lithium niobate target and stainless steel plate;

[0066] Step 2, depositing a lithium niobate piezoelectric coating; depositing for 480 min at a radio frequency power of 900 W, a deposition pressure of 2.0 Pa, an Ar / O2 flow ratio of 2 / 1, a deposition temperature of 200° C., and a target-base distance of 5 cm, to deposit a 13.4 μm lithium niobate piezoelectric coating on the surface of the stainless steel plate;

[0067] Step 3, depositing a pre-plated coating: using a high-purity Cr target, depositing for 1 min at an arc current of 90 A, an Ar gas flow rate of 1.0 Pa, a deposition temperature of 45° C., and a target-base distance of 120 mm, to deposit a 100 nm pre-plated Cr coating on the surface of the lithium niobate piezoelectric coating;

[0068] Step 4, depositing the electrode coating: using a high-purity Ag target, depositing for 20 minutes at an RF power of 700 W, an Ar gas flow rate of 1.0 Pa, a deposition temperature of 45°C, and a target-substrate distance of 80 mm, adding a bias voltage at the beginning of deposition for 1 minute (the substrate potential is lower than the target, the voltage is 200 V, the duty cycle is 30%, and the current is 0.4 A) to promote the energy-carrying Ag ions to enter the Cr coating, forming a mixed zone of the Cr coating and the Ag coating with a thickness of about 20 nm to increase the bonding; then remove the bias voltage until the deposition is completed, and deposit a 10 μm Ag coating on the surface of the pre-plated Cr coating to obtain a sensor with enhanced ultrasonic reflection echo.

[0069] Embodiments 6 to 10

[0070] It is basically the same as Example 5, with the only difference being that the deposition time in step 4 is 40 min, 60 min, 80 min, 100 min and 120 min, respectively, and the prepared Ag coating has an enhanced ultrasonic reflection echo sensor with a thickness of 20 μm, 30 μm, 40 μm, 50 μm and 60 μm, respectively.

[0071] The ultrasonic signals and ultrasonic frequencies (excitation voltage of 200 V) of the sensors for enhancing ultrasonic reflection echo prepared in Examples 5 to 10 were tested. The results are as follows: Figure 3 shown. Figure 3 (a) is the ultrasonic signal diagram, Figure 3 (b) Ultrasonic echo frequency, Figure 3 (c) Ultrasonic signal amplitude and frequency numerical line graph, Figure 3 (d) is the corresponding time of flight (TOF) data. It can be seen that:

[0072] 1. As the deposition time of the Ag coating increases (i.e., the thickness gradually increases), the frequency of the ultrasonic wave gradually decreases (from 26Mhz to 13.5MHz).

[0073] 2. For the reflected ultrasonic amplitude, when the thickness of the Ag coating is less than 40μm, it will first gradually increase with the increase of the Ag coating deposition time (that is, the thickness gradually increases), from 0.85V to 1.45V, because the thicker the electrode coating, the higher the coating quality, and at the same time the ultrasonic frequency is reduced, so that the signal attenuation is weakened, which is conducive to the extraction of stronger sound wave signals; when the thickness of the Ag coating is higher than 40μm, the ultrasonic signal is weakened, because the excessive thickness of the electrode layer will cause excessive stress, fall off, and reduce the conductivity, which is not conducive to the extraction of ultrasonic signals.

[0074] 3. As the deposition time of the Ag coating increases (i.e., the thickness gradually increases), the ultrasonic echo shifts to the right, that is, the TOF also increases with the deposition time of the coating (from 0.277μs to 0.323μs). The increase in TOF means that the ultrasonic transmission distance increases, and the thickness of the Ag coating can be calculated by the increase in TOF. These results show that the thickness of the Ag coating can be adjusted to reduce the ultrasonic frequency, so as to reduce the absorption of the stainless steel plate to the sound wave energy, thereby increasing the amplitude of the reflected ultrasonic wave and realizing the stress detection of the stainless steel plate.

[0075] Embodiment 11

[0076] A method for preparing a thin film sensor for enhancing ultrasonic reflection echo, the steps are as follows:

[0077] Step 1: Prepare the magnetron sputtering equipment: place the lithium niobate target and stainless steel plate;

[0078] Step 2, depositing a lithium niobate piezoelectric coating; depositing for 480 min at a radio frequency power of 900 W, a deposition pressure of 1.5 Pa, an Ar / O2 flow ratio of 2 / 1, a deposition temperature of 150° C., and a target-base distance of 5 cm, to deposit a 13.7 μm lithium niobate piezoelectric coating on the surface of the stainless steel plate;

[0079] Step 3, depositing electrode coating: using high-purity Ag target material, depositing for 20 min at a RF power of 700 W, an Ar gas flow rate of 1.0 Pa, a deposition temperature of 45 ° C, and a target-base distance of 80 mm, depositing a 10 μm Ag coating on the surface of the lithium niobate piezoelectric coating to obtain a sensor with enhanced ultrasonic reflection echo.

[0080] Example 12 to Example 14

[0081] It is basically the same as Example 11, with the only difference being that in step 3, the deposition time is 40 min, 60 min and 80 min, respectively, and the prepared sensors have Ag coating thicknesses of 20 μm, 30 μm and 40 μm, respectively, for enhanced ultrasonic reflection echo.

[0082] The ultrasonic signals and ultrasonic frequencies (excitation voltage is 200V) of the sensors for enhancing ultrasonic reflection echo prepared in Examples 11 to 14 were tested. The results are as follows: Figure 4 shown. Figure 4 (a) is the ultrasonic signal diagram, Figure 4 (b) Ultrasonic echo frequency, Figure 4 (c) Ultrasonic signal amplitude and frequency numerical line graph, Figure 4 (d) is the corresponding TOF data. It can be seen that:

[0083] 1. As the deposition time of the Ag coating increases (i.e., the thickness gradually increases), the frequency of the ultrasonic wave still gradually decreases (from 25Mhz to 13MHz).

[0084] 2. Amplitude of reflected ultrasonic wave: The optimal Ag coating thickness decreases from 40μm to 20μm, that is, when the Ag coating thickness is less than 20μm, the acoustic wave amplitude gradually increases with the increase of Ag coating thickness; when the Ag coating thickness is higher than 20μm, the ultrasonic signal weakens.

[0085] 3. As the deposition time of the Ag coating increases (i.e., the thickness gradually increases), the ultrasonic echo still shifts to the right, that is, the TOF also increases with the increase in the deposition time of the coating. The thickness increase of the Ag coating can also be calculated by the TOF increase value.

[0086] Embodiment 15

[0087] A method for preparing a thin film sensor for enhancing ultrasonic reflection echo, the steps are as follows:

[0088] Step 1: Prepare the magnetron sputtering equipment: place the lithium niobate target and stainless steel plate;

[0089] Step 2, depositing a lithium niobate piezoelectric coating; depositing for 480 min at a target bias of -6.0 V (the substrate potential is 6 V lower than the target potential), a radio frequency power of 900 W, a deposition pressure of 2.0 Pa, an Ar / O2 flow ratio of 2 / 1, a deposition temperature of 150° C., and a target-base distance of 5 cm, to deposit a 9.3 μm lithium niobate piezoelectric coating on the surface of the stainless steel plate;

[0090] Step 3, depositing electrode coating: using high-purity Ag target material, depositing for 20 min at a RF power of 700 W, an Ar gas flow rate of 1.0 Pa, a deposition temperature of 45 ° C, and a target-base distance of 80 mm, depositing a 10 μm Ag coating on the surface of the lithium niobate piezoelectric coating to obtain a sensor with enhanced ultrasonic reflection echo.

[0091] Example 16 to Example 18

[0092] It is basically the same as Example 15, with the only difference being that in step 3, the deposition time is 40 min, 60 min and 80 min, respectively, and the prepared sensors have Ag coating thicknesses of 20 μm, 30 μm and 40 μm, respectively, for enhanced ultrasonic reflection echo.

[0093] The ultrasonic signals and ultrasonic frequencies (excitation voltage of 200 V) of the sensors for enhancing ultrasonic reflection echo prepared in Examples 15 to 18 were tested. The results are as follows: Figure 5 shown. Figure 5 (a) is the ultrasonic signal diagram, Figure 5 (b) Ultrasonic echo frequency, Figure 5 (c) Ultrasonic signal amplitude and frequency numerical line graph, Figure 5 (d) is the corresponding TOF data. It can be seen that the variation pattern is consistent with that of Examples 11 to 14, which proves that the repeatability of the preparation method of the present invention is feasible.

[0094] In addition, comparing the use results of Examples 5 to 10 (with pre-plated Cr coating), Examples 11 to 14 (without pre-plated Cr coating), and Examples 15 to 18 (without pre-plated Cr coating), the optimal Ag coating thickness of Examples 5 to 10 is 40 μm, and the optimal Ag coating thickness of Examples 11 to 14 and Examples 15 to 18 is reduced to 20 μm, and the deposited Ag coating will fall off prematurely. The presence of pre-plated Cr coating can well enhance the bonding force of Ag coating, but without pre-plated Cr, it is also possible to appropriately increase the thickness of the electrode layer to obtain a higher coating quality and reduce the sensor acoustic wave frequency, thereby enhancing the effect of ultrasonic reflection echo, but the effect is weaker than the case with pre-plated Cr.

[0095] Embodiment 19

[0096] A method for preparing a thin film sensor for enhancing ultrasonic reflection echo, the steps are as follows:

[0097] Step 1: Prepare the magnetron sputtering equipment: place the lithium niobate target and stainless steel plate;

[0098] Step 2, depositing a lithium niobate piezoelectric coating; depositing for 480 min at a radio frequency power of 800 W, a deposition pressure of 2.0 Pa, an Ar / O2 flow ratio of 2 / 1, a deposition temperature of 150° C., and a target-base distance of 5 cm, to deposit a lithium niobate piezoelectric coating of 11.4 μm on the surface of the stainless steel plate;

[0099] Step 3, depositing a pre-plated coating: using a high-purity Cr target, depositing for 2 min at an arc current of 90 A, an Ar gas flow rate of 1.0 Pa, a deposition temperature of 45° C., and a target-base distance of 120 mm, to deposit a 200 nm pre-plated Cr coating on the surface of the lithium niobate piezoelectric coating;

[0100] Step 4, depositing electrode coating: using high-purity AgCr target material, depositing for 60 min at a RF power of 700 W, an Ar gas flow rate of 1.0 Pa, a deposition temperature of 45 ° C, and a target-substrate distance of 80 mm, adding bias voltage at the beginning of deposition for 1 min (the substrate potential is lower than the target material, the voltage is 200 V, the duty cycle is 30%, and the current is 0.4 A) to promote the energy-carrying Ag ions and Cr ions to enter the Cr coating, forming a mixed zone of Cr and AgCr with a thickness of about 20 nm, thereby increasing the bonding; then removing the bias voltage until the deposition is completed, and depositing a 9 μm AgCr coating on the surface of the pre-plated Cr coating to obtain a sensor with enhanced ultrasonic reflection echo.

[0101] Example 20 to Example 24

[0102] It is basically the same as Example 19, with the only difference being that in step 3, the deposition time is 120 min, 180 min, 240 min, 300 min and 420 min, respectively, and the prepared AgCr coating has an enhanced ultrasonic reflection echo sensor with a thickness of 18 μm, 27 μm, 36 μm, 45 μm and 63 μm, respectively.

[0103] The ultrasonic signals and ultrasonic frequencies (excitation voltage of 200 V) of the sensors for enhancing ultrasonic reflection echo prepared in Examples 19 to 24 were tested. The results are as follows: Figure 6 shown. Figure 6 (a) is the ultrasonic signal diagram, Figure 6 (b) Ultrasonic echo frequency, Figure 6 (c) Ultrasonic signal amplitude and frequency numerical line graph, Figure 6 (d) is the corresponding TOF data. It can be seen that:

[0104] 1. As the deposition time of the AgCr coating increases (i.e., the thickness gradually increases), the frequency of the ultrasonic wave still gradually decreases (also from 26.5Mhz to 13.5MHz).

[0105] 2. Amplitude of reflected ultrasonic wave: When the thickness of AgCr coating is lower than 45μm, it will first increase gradually with the increase of AgCr coating deposition time (i.e., the thickness gradually increases), from 0.3V to 1.4V, because the thicker the electrode layer, the higher the coating quality, and at the same time the ultrasonic frequency decreases, so that the signal attenuation is weakened, which is conducive to the extraction of stronger sound wave signals; when the thickness of AgCr coating is higher than 45μm, the ultrasonic signal weakens, because the excessive thickness of AgCr coating will cause excessive stress, fall off, and reduce the conductivity, which is not conducive to the extraction of ultrasonic signals.

[0106] 3. As the deposition time of the AgCr coating increases (i.e., the thickness gradually increases), the ultrasonic echo also shifts to the right, that is, the TOF also increases with the increase in the coating deposition time (from 0.268μs to 0.300μs). The increase in TOF means that the ultrasonic transmission distance increases. The thickness of the AgCr coating can be calculated by the TOF increase value.

[0107] In summary, the present invention adjusts the thickness of the electrode coating by adjusting the deposition time, increases the coating quality, and reduces the ultrasonic frequency to reduce the absorption of the sound wave energy by the stainless steel material and the high-temperature alloy bolt, thereby increasing the amplitude of the reflected ultrasonic wave, and can realize the stress detection of the stainless steel bolt and the high-temperature alloy bolt. In addition, the thickness of the electrode coating can also be adjusted by the radio frequency power, deposition pressure, deposition temperature, and target-base distance, as shown in the following embodiments.

[0108] Embodiment 25

[0109] A method for preparing a thin film sensor for enhancing ultrasonic reflection echoes. The invention also provides a method for regulating the deposition rate (ie thickness) of an electrode coating by means of parameters.

[0110] Ag, Cu, Cr, Ti, Al, and AgCr targets were selected to deposit the corresponding electrode coatings. The RF power was 700W, the Ar gas flow rate was 1.0Pa, the deposition temperature was 40°C, the deposition time was 40min, and the target-substrate distance was regulated between 40mm and 100mm. The thickness of each coating was measured to obtain the relationship between the deposition rate of each coating and the target-substrate distance.

[0111] Figure 7 The relationship between the deposition rate of Ag, Cu, Cr, Ti, Al, and AgCr electrode coatings and the target-substrate distance is shown in the figure. It can be seen that the deposition rates of the electrode coatings are different, but they all have the same variation law with the target-substrate distance, which is almost close to a linear relationship. Therefore, under the condition of fixing other deposition parameters, the ideal electrode coating thickness can be obtained by adjusting the target-substrate distance to adjust the sensor acoustic wave frequency and the reflected echo amplitude.

[0112] Embodiment 26

[0113] A thin film sensor structure for enhancing ultrasonic reflection echo and a preparation method thereof. The invention also provides a method for regulating the deposition rate (ie thickness) of an electrode coating by means of parameters.

[0114] Ag and Cr targets were selected to deposit the corresponding electrode coatings, with an Ar gas flow of 1.0 Pa, a deposition temperature of 40°C, a deposition time of 40 min, a target-substrate distance of 70 mm, and RF power adjusted between 300 W and 900 W. The thickness of each coating was measured to obtain the relationship between the deposition rate of each coating and the RF power.

[0115] Figure 8 The relationship between the deposition rate of Ag and Cr functional coatings and RF power is shown in Figure 1. It can be seen that the deposition rates of the two electrode coatings are different, but they have the same variation law with the RF power, which is almost a linear relationship. Therefore, under the condition of fixing other deposition parameters, the ideal functional layer thickness can be obtained by regulating the RF power to regulate the sensor acoustic wave frequency and the reflected echo amplitude.

[0116] In addition, by adjusting the Ar gas flow, deposition temperature and other deposition parameters, the thickness and deposition rate of Ag, Cu, Cr, Ti, Al and AgCr functional coatings were also controlled.

[0117] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A thin film sensor for enhancing ultrasonic reflection echo, characterized in that: From bottom to top, it includes substrate, piezoelectric coating and electrode coating; The electrode coating has a thickness of 5 to 100 μm and is prepared by magnetron sputtering; the composition of the electrode coating includes at least one of Ag, Cu, Cr, Ti or Al; The preparation of electrode coating includes, The deposition time was 10-500 min at RF power of 300-900 W, Ar gas flow of 0.6 Pa-2.0 Pa, deposition temperature of 40-150 ° C, and target-substrate distance of 40 mm-90 mm. There is also a 50-200 nm pre-plating coating between the piezoelectric coating and the electrode coating; The method for preparing the pre-plating coating comprises: The arc ion plating method is adopted, with an arc current of 80~120A, an Ar gas flow rate of 0.6~2.0Pa, a deposition temperature of 40~150℃, a target-substrate distance of 100~200mm, and a deposition time of 30s~2min; The pre-plating coating comprises at least one of Cr, Ti or Al; There is also a mixed zone of the pre-plating coating and the electrode coating between the pre-plating coating and the electrode coating; The mixed area of ​​the pre-plating coating and the electrode coating is formed by adjusting the duty cycle to 20% to 50%, the current to 0.2A to 0.8A, and applying a bias voltage of 100 to 300V during the initial 30s to 2min of preparing the electrode coating by magnetron sputtering; The thickness of the mixed area of ​​the pre-plating coating and the electrode coating is 10-30 nm; The composition of the piezoelectric coating includes one of ZnO, AlN, AlScN, and LiNbO3; The method for preparing the piezoelectric coating comprises: The RF power is 500~900W, the deposition gas pressure is 0.6Pa~2.0Pa, the flow ratio of Ar gas to functional gas is 3 / 1~1 / 3, the deposition temperature is 40~250℃, the target-substrate distance is 30mm~90mm, and the deposition time is 10~500min.

2. The thin film sensor for enhancing ultrasonic reflection echo according to claim 1, characterized in that: The substrate comprises a stainless steel plate and high-temperature alloy bolts.

3. Application of the thin film sensor with enhanced ultrasonic reflection echo as claimed in claim 1 in stress detection.

Citation Information

Patent Citations

  • LiNbO3 / LiTaO3 piezoelectric coating sensor and preparation method thereof

    CN115184453A

  • Intelligent cloud bolt for high-precision pretightening force monitoring and preparation method thereof

    CN115452234A